Applying a reproducible research approach to distance education - M. A. Eremeev; O. V. Trubienko; I. I. Zakharchuk (Российский технологический журнал)
Objectives. Emerging as a response to the global threats presented by the COVID-19 pandemic, the changing nature of problem-solving in the field of information technology associated with economic globalization, including possibilities of remote working, imposes new requirements on the competencies and skills of future professionals. This, in turn, requires adjustments to the higher education process. Agile project management methodologies such as Scrum, along with Infrastructure-as-Code approaches in information and telecommunication infrastructure management, and Documentation-as-Code approaches in documentation development, aim to present design, development, testing, and documentation as short cycle iterative processes to permit the rapid and transparent addition of new product value in discrete portions. Applied to the education sphere, this approach implies new knowledge and practical skills of students that can be easily and transparently measured in the process of mastering a discipline. The present paper aims to develop methods of applying modern software development techniques to training students of technical specialties.Methods. The use of reproducible research methods and agile design practices while organizing and managing practical tasks for students is proposed.Results. Contemporary tools used in software development based on Git hosting services (GitLab and GitHub) are presented alongside reproducible research paradigms in distance education using the R Markdown format by RStudio.Conclusions. In addition to increasing the involvement of students in the process of practical tasks, the proposed approach can be used to reduce the workload of teachers when checking and evaluating student working results.